2015
DOI: 10.1177/0107408314560323
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to take care of HIV positive people: Responses from Russian nursing students

Abstract: This article is a report of a study on Russian nursing students’ willingness to take care of people living with HIV or AIDS (PLWHA). HIV and AIDS are continuing to spread in Russia. Nursing students’ willingness to care for people living with HIV or AIDS is one aspect that should also be taken in consideration on this transmission situation. In total, 102 nursing students participated in the study (the response rate was 95.3%). The data were collected using the Nurse Willingness Questionnaire (NWQ) and analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…These multiple roles can lead to less time for caring for PLHA. This finding is in accordance with previous research that states that respondents who work have less time to pay attention to and are less willing to care for PLHA (Suominen et al, 2015;Välimäki et al, 2008). However, good cooperation between residents and the local government can provide solutions that allow such individuals to pay attention to the welfare of and care for PLHA so that they can have a better quality of life.…”
Section: Discussionsupporting
confidence: 92%
“…These multiple roles can lead to less time for caring for PLHA. This finding is in accordance with previous research that states that respondents who work have less time to pay attention to and are less willing to care for PLHA (Suominen et al, 2015;Välimäki et al, 2008). However, good cooperation between residents and the local government can provide solutions that allow such individuals to pay attention to the welfare of and care for PLHA so that they can have a better quality of life.…”
Section: Discussionsupporting
confidence: 92%
“…Since the earliest study examining student and faculty attitudes about caring for PLHIV (Mueller, Cerny, Amundson, & Waldron, 1992), there have been fewer than 20 additional studies reported in the literature (PubMed ® and SciELO searches). However, the results of the few studies often report only students in small local samples using a validated, although outdated, instrument (Bektas & Kulakaç, 2007;Earl, 2010;Li, Scott, & Li, 2008;Lohrmann et al, 2000;Röndahl, Innala, & Carlsson, 2003;Suominen, Laakkonen, & Lioznov, 2015).…”
mentioning
confidence: 99%